HPV type‐specific distribution among family members and linen in households of cutaneous wart patients. (2nd October 2021) - Ghorzang, E.; de Koning, M.N.C.; Bouwes Bavinck, J.N.; Gussekloo, J.; Quint, K.D.; Goeman, J.J.; Feltkamp, M.C.W.; Bruggink, S.C.; Eekhof, J.A.H.
Abstract: Background: Common and plantar warts are caused by human papillomaviruses (HPV). Mode of transmission of wart HPVs within families is largely unknown. Objective: To demonstrate similarity of HPV type(s) among wart cases, family members and household linen. Methods: In a cross‐sectional study, swabs taken from 123 warts and foreheads of 62 index patients and 157 family members and from 58 kitchen towels and 59 bathroom mats were tested for DNA of 23 cutaneous wart‐associated HPV types. Generalized estimating equations (GEE) were used to estimate the chance of detecting the same HPV type as was found in the index patients on the family contacts and on the kitchen towels and bathroom mats. Results: HPV1, HPV2, HPV27 and HPV57 were the most prevalent types in the warts of the index patients. Altogether, 60 (42.3%) of the 142 family members without warts had HPV DNA on their foreheads. When HPV1 and HPV2 were found in the warts, these types were also frequently (>50%) found on the foreheads of index patients and their family members, as well as on the kitchen towels and the bathroom mats. HPV27 and HPV57 were less frequently found (<25%) on foreheads and linen. No associations were found for age, sex and site of HPV DNA presence. Conclusion: Dissemination of skin wart‐causing HPV types, from wart cases to household contacts and linen, such as kitchen towels and bathroom mats, is more likely for HPV1 and HPV2 than for HPV27 and HPV57. The role of towels and bathroom mats in HPV transmission deserves further investigation. Abstract : Linked Commentary A. Kreuter and U. Wieland. J Eur Acad Dermatol Venereol 2022; 36 : 11–12. https://doi.org/10.1111/jdv.17820 .